2012
DOI: 10.3945/ajcn.112.040717
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral lipid administration to very-low-birth-weight infants—early introduction of lipids and use of new lipid emulsions: a systematic review and meta-analysis

Abstract: The initiation of lipids within the first 2 d of life in VLBW infants appears to be safe and well tolerated; however, beneficial effects on growth could not be shown for this treatment nor for the type of lipid emulsion. Emulsions that are not purely soybean oil-based might be associated with a lower incidence of sepsis. Large-scale randomized controlled trials in preterm infants are warranted to determine whether early initiation of lipids and lipid emulsions that are not purely soybean oil-based results in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 47 publications
7
72
0
9
Order By: Relevance
“…1,5,[13][14][15][16] Lipids emulsions help to reach the high caloric requirements of preterm and are the unique source of essential fatty acids. Lipids should account for 25-40% of non-protein calories.…”
Section: Lipidsmentioning
confidence: 99%
“…1,5,[13][14][15][16] Lipids emulsions help to reach the high caloric requirements of preterm and are the unique source of essential fatty acids. Lipids should account for 25-40% of non-protein calories.…”
Section: Lipidsmentioning
confidence: 99%
“…35 A systematic review of the early introduction of lipids (defined as introduction within the first 2 days after birth) and the use of new lipid emulsions included 14 RCTs. 36 Early initiation of lipids had no impact on any of the outcome measures, including death, bronchopulmonary dysplasia, necrotising enterocolitis, patent ductus arteriosus, sepsis, intraventricular haemorrhage, significant jaundice and hypertriglyceridaemia. The meta-analysis of the effects of lipid emulsions that are not purely soya bean based showed no difference in outcomes of death, duration of respiratory support or rate of weight gain.…”
Section: Previous Studies Of Parenteral Nutritionmentioning
confidence: 99%
“…However, the authors concluded that large-scale RCTs are needed to determine the efficacy of newer lipids. 36 We recently published a systematic review of preterm PN summarising the evidence to date. 37 The review concludes that the evidence base for current recommendations is based on historical evidence and there are no long-term studies of the impact of PN on health and neurodevelopment.…”
Section: Previous Studies Of Parenteral Nutritionmentioning
confidence: 99%
“…La introducción precoz de soluciones lipídicas (entre 12 horas y 2 días tras el nacimiento) ha mostrado ser segura comparada con la introducción tardía (16,17), mejorar el balance nitrogenado y revelar una tendencia a menor tasa de hiperglucemia (16).…”
Section: Requerimientos De Lípidosunclassified
“…Respecto a la composición de la emulsión lipídica en RN, la comparación de aquellas basadas en aceite de oliva, aceite de pescado y las mezclas de aceite de soja con triglicéridos de cadena media (MCT) (16), han mostrado ser seguras frente a las procedentes de soja, con una incidencia similar de efectos adversos. Estas mezclas alternativas presentan beneficios desde un punto de vista fisiopatológico, como disminución del estrés oxidativo, reducción del contenido en fitoesteroles, activación del sistema retículo-endotelial (18) o vasodilatación pulmonar, que han sido demostrados en ensayos clínicos en modelos animales (19) y/o RN prematuros (20).…”
Section: Requerimientos De Lípidosunclassified